(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The industrial project is about extraction of content from pictures, which is acknowledgment of characters in electronic or mechanical transformation of pictures of composed, manually written or printed text into machine encoded text, regardless of whether from a checked archive, a photograph of a record, a scene- photograph (for instance the content on signs and announcements in a scene photograph) or from caption text superimposed on picture. Broadly utilized as type of information section from printed paper information – regardless of whether identification reports, solicitations, bank explanations, automated receipts, N business cards, mail, printouts of static-information, or an appropriate documentation m– it is a typical technique for digitizing printed messages with the goal that they can be e electronically altered, put away more minimalistic ally, showed online, and utilized in machine cycles, machine interpretation, (removed) text to- discourse, key information and text mining. OCR is a field of exploration in example acknowledgment, computerized reasoning and PC vision. The primary goal of this task is to create AI calculation to empower element and information extraction from records with manually written explanations, with an expect to distinguish transcribed words on a picture.